Total Phenolic of Postbiotics from Rhizopus oligosporus with Edamame Husk Substrate (Glycine max (L.) Merrill) - Prasetyo, Angga; Rasmiyana, Rasmiyana; Frengky Hermawan Hadi Prasetyo (Jurnal Biologi Tropis, 2025)
Edamame husk (Glycine max (L.) Merrill) is an agro-industrial waste product rich in carbohydrates complex, therefore potentially suitable as a substrate for postbiotics production using the fungus R. oligosporus. Postbiotics are the latest generation of biotics consisting of inanimate microbial cells along with their metabolites. This study aimed to determine the total phenolic content of postbiotics generated from R. oligosporus using edamame husk as substrate through submerged fermentation for 5 days. Fermentation was conducted using variations in spore inoculum volume (0; 0,5; 1; 1,5 ml at a concentration 1 x 106 spores/ml). The produced postbiotics were then subjected to heat treatment at 121oC for 15 minutes using autoclave and analyzed for total phenolic content using the Folin-Ciocalteu method. The measurement results showed that the addition of 1,5 ml of spores R. oligosporus produced the highest total phenolic content and was significantly different from the other treatments. Viability testing of R. oligosporus after heat treatment showed no growth on PDA medium after 21 days of incubation, thus met one of the criteria for postbiotics. These findings indicate that edamame husk have potential as an alternative raw material in the production of postbiotics using R. oligosporus.